Creating a Digital Model of the Damages of the Earthquake of Metropolitan Tarnovo /13th century/ - Robov, Mirko (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2016)
The studying of the monuments and complexes in Tarnovo, as well as some other examples in its vicinity give us some strong points for determining of earthquakes and provide data for developing a digital model for this natural phenomenon in the urban environment, in accordance with the specific natural characteristics.